1998
DOI: 10.1006/dbio.1997.8793
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Analysis of Hyalin—A Substrate for Cell Adhesion in the Hyaline Layer of the Sea Urchin Embryo

Abstract: The hyaline layer of echinoderm embryos is an extraembryonic matrix that functions as a substrate for cell adhesion through early development. The major constituent of the hyaline layer is the protein hyalin, a fibrillar glycoprotein of approximately 330 kDa that multimerizes in the presence of calcium. Here we provide a molecular characterization of hyalin and identify a region of the protein that is important for its function in cell adhesion. Partial hyalin cDNAs were identified from two sea urchin species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 4 publications
3
78
1
Order By: Relevance
“…The hyalin repeat domain is thought to be a distinct superfamily within the immunoglobulin-like fold and is believed to function in cell adhesion (Wessel et al, 1998;Callebaut et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The hyalin repeat domain is thought to be a distinct superfamily within the immunoglobulin-like fold and is believed to function in cell adhesion (Wessel et al, 1998;Callebaut et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In a single cell assay, using cells dissociated from L. variegatus sea urchin embryos, it was found that cells bound to both native hyalin or a bacterially expressed recombinant hyalin repeat, which does not contain carbohydrate (Wessel et al, 1998). An anti-hyalin monoclonal antibody (Tg-HYL (McAb183) blocked cell binding to both native and recombinant hyalin (Wessel et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…An anti-hyalin monoclonal antibody (Tg-HYL (McAb183) blocked cell binding to both native and recombinant hyalin (Wessel et al, 1998). This same antibody caused cells in vivo to retract from the hyaline layer, blocking gastrulation (Adelson and Humphreys, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations